Farm wages and public works. Issue 1 (13th April 2015) - Mahajan, Kanika
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the impact of National Rural Employment Guarantee Scheme (NREGS) on farm sector wage rate. This identification strategy rests on the assumption that all districts across India would have had similar wage trends in the absence of the program. The author argues that this assumption may not be true due to non-random allocation of districts to the program's three phases across states and different economic growth paths of the states post the implementation of NREGS. Design/methodology/approach – To control for overall macroeconomic trends, the author allows for state-level time fixed effects to capture the differences in growth trajectories across districts due to changing economic landscape in the parent-state over time. The author also estimates the expected farm sector wage growth due to the increased public work employment provision using a theoretical model. Findings – The results, contrary to the existing studies, do not find support for a significantly positive impact of NREGS treatment on private cultivation wage rate. The theoretical model also shows that an increase in public employment work days explains very little of the total growth in cultivation wage post 2004. Originality/value – This paper looks specifically at farm sector wage growth and the possible impact of NREGS on it, accounting for state specific factors in shaping farm wages. Theoretical estimates are presented to overcome econometric limitations.